Theoretical Investigation on the Antioxidant Activity of p-Cresol and Its Derivatives: Effects of Propenyl Group and Solvents (Journal of Atomic and Molecular Sciences, 2018)
The effect of propenyl group on the antioxidant activity of p-cresol and its derivatives were investigated in gas and solvent phases by using density functional theory (DFT) method. Three accepted antioxidant mechanisms, including hydrogen atom transfer (HAT), single-electron transfer followed by proton transfer (SET-PT) and sequential proton loss electron transfer (SPLET), were considered to explore which mechanism p-cresol and its derivatives preferred to in different environments. The bond dissociation enthalpy (BDE), ionization potential (IP), proton dissociation enthalpy (PDE), proton affinity (PA) and electron transfer enthalpy (ETE), closely related to the above three antioxidant mechanisms, were calculated systematically. The obtained results indicate that the antioxidant process of studied compounds prefers to the SET-PT and SPLET mechanism in gas phase and polar solvents, respectively. Meaningfully, the introduction of the propenyl group into the molecular structure can reduce the PA values and then improve the antioxidant activity of the studied compounds, which can provide theoretical guidance for the synthesis of novel antioxidants in the experiment.